A highly efficient fire‐retardant nanomaterial based on carbon nanotubes and magnesium hydroxide. (31st January 2012) - Knight, Chase C.; Ip, Filbert; Zeng, Changchun; Zhang, Chuck; Wang, Ben
SUMMARY Hybrid buckypapers (HBP) were developed and showed potential as efficient fire‐retardant materials by implementing multiple fire retardance mechanisms. The fabrication of HBP was performed using multi‐walled carbon nanotubes (MWCNTs) and magnesium hydroxide (Mg(OH)2) nanoparticles. The Mg(OH)2 nanoparticles were well dispersed throughout the CNTs network, as revealed by scanning electron microscopy and Energy Dispersive X‐ray spectroscopy. Thermogravimetric analysis and differential scanning calorimetry both confirmed the decomposition of magnesium hydroxide in the HBPs and heat absorption under elevated temperatures. Our initial results indicated that when used as a skin layer, the HBP has the potential to significantly improve the fire‐retardant properties of epoxy carbon fiber composites. Copyright © 2012 John Wiley & Sons, Ltd.